Strong motion observation at Middle Marsyangdi Hydroelectric Project dam, Lamjung, western Nepal - Rajaure, S.; Paudel, T. R.; Bhattarai, G. K. (Journal of Nepal Geological Society, 2011)
Middle Marsyangdi Hydroelectric Project (MMHEP) of the Nepal Electricity Authority (NEA) has installed a network of four strong motion seismometers (accelerometers) at its darn site. The network has recorded two earthquakes of local magnitudes (ML) 4.0 and 4.3 on 13’h of April in 2009. These earthquakes occurred at less than 20 km hypocentral distance from the darn site. Analysis and interpretation of the ML4.3 earthquake only are presented in this paper because the other earthquakes are closely spaced and the spectral characteristics are similar. The maximum acceleration (28 gal, 1 gal = 9.8cm/sec2 is recorded by the north-south component of accelerometer installed at the crest of rock-fill dam (Acc- I ) and the smallest acceleration is recorded by north-south component of Acc-4 installed on the hard rock. Spectral amplification of up to 18 is observed, at 3.33 Hz, on the N-S component of accelerometer (Acc-2), which is installed at the concrete dam-crest. Similarly, the maximum amplification of peak acceleration of about 8 is observed on N-S component of Ace- 1. The variations observed in se is mic parameters, recorded at different parts of the dam, reflect the response of the different parts of the structure to the input seismic motion.